Artificial Intelligence Influencers: Navigating Digital Identity and Sustainability in the Era of AI - Moise, Daniel; Mănescu, Andreea Maria; Moncea, Mădălina Ioana; Chiotan, Florin (European Journal of Sustainable Development, 2025)
The appearance and development of Artificial Intelligence will reshape the world, and will have an impact on PESTELI: Political, Economic, Socio-cultural, Technological, Ecological, Legislative and Industry, sectors in ways never witnessed before. Organizations, no matter if they are for-profit companies, or non-profit organizations, politicians, parties, VIPs, influencers, or even ordinary people, will try to enhance their presence online. This is done to gain more profit and increase brand awareness, notoriety, and even acceptance by the general public. The development of AI provides a tremendous boost to those who use social media networks and want to get in contact with their stakeholders. In this study, we conducted research to determine the audience’s level of acceptance toward influencers who either use artificial intelligence for certain features, or rely entirely on AI-generated content. Many of the respondents mentioned that they prefer genuine influencers, while AI-driven avatar influencers should have a distinctive symbol. We have created a classification of influencers who use AI tools, based on the way and percentage of their use of such features. Digital Marketing Influencers can transform brand communication and engagement, not only for a product or service, but for an idea, acceptance, and even for a politician or a party. Keywords: artificial intelligence, real influencers, non-human influencers, social media networks, classification of influencers by AI usage